Analysis of Weaknesses and Strengths Online Learning Faculty of Letters State University of Malang - Ilham Mohamad Rijal Arosyd; Rizman - Rizman (Universitas Negeri Malang, 2020)
This study aims to describe the online learning process at the Faculty of Letters, State University of Malang using quantitative methods. The data collection technique in this study used a questionnaire in google form which was distributed via WhatsApp messages. Determination of the sample in this study using accidental sampling. The sample used was 115 students of the Faculty of Letters, State University of Malang. The results showed that there were several strengths and weaknesses such as getting additional material, easier access to material, assistance to access paid material from the university, online learning materials presented in several forms, interactive online learning processes, and good learning outcomes..